PENGARUH KINERJA KEUANGAN PEMERINTAH DAERAH TERHADAP BELANJA MODAL UNTUK PELAYANAN PUBLIK (Studi pada kabupaten dan kota di Provinsi Sulawesi Utara) - Tamawiwy, Julius; Sondakh, Jullie J; Warongan, Jessy D.L (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2016)
The main objective of regional autonomy is to improve public services and promote the local economy in Indonesia. Capital expenditures for public services is used to finance expenditure in investing activities (add assets) aimed at improving public infrastructure that results can be used directly by the public. Developed regions tend to maintain the structure of expenditure into maintenance expenditure. The shift in spending patterns in the local government often triggered concerns about the extent to which the amount of local revenue affects the pattern of local government spending, especially capital expenditure for public services. This study purposes to analyze growth of revenue (PAD), the ​​fiscal decentralization, financial effectiveness and efficiency of the Local Government Financial Management to the capital expenditure for public services. The method used is quantitative method with a sampling technique using judgment sampling which took samples with consideration of the availability of data in the Local Government Financial Statements Reports in the Province of North Sulawesi by 10 districts/cities of Local Government in North Sulawesi since 2010 to 2015. The analytical method used is a multiple regression using SPSS 20 application assistance. The results show that PAD  growth is effect as positive and significant capital expenditures for public services, fiscal decentralization is negative effect and not significant toward capital expenditures for public services, effectiveness  and efficiency of local financial is  effect as positive but not significant toward capital expenditures for public services..